The Pointed Challenge: Endoscopic Management of an Ingested Sharp Foreign Body and a Synthesis of Modern Techniques - Sindhu Nugroho Mukti; Sigit Adi Prasetyo; Bernardus Parish Budiono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The ingestion of sharp-pointed foreign bodies constitutes a high-acuity medical emergency, distinguished from other ingested objects by its significant potential for severe complications, including visceral perforation and hemorrhage. While flexible endoscopy has emerged as the cornerstone of management, its successful application hinges on a systematic, protocol-driven approach. This manuscript presents a case of an ingested straight pin and uses it as the framework for a critical synthesis of modern diagnostic and therapeutic strategies. Case presentation: A 40-year-old female presented to the emergency department, hemodynamically stable and completely asymptomatic, two hours after accidentally swallowing a straight pin. A benign abdominal examination belied the potential danger. Plain radiography confirmed a single, sharp metallic object in the gastric antrum. An urgent esophagogastroduodenoscopy under general anesthesia was performed. The pin was securely grasped with rat-tooth forceps and extracted without incident. The patient's recovery was uneventful, and she was discharged on the first postoperative day. Conclusion: This case provides a high-fidelity validation of current international guidelines, demonstrating that a protocol-driven approach—encompassing rapid triage, definitive imaging, and urgent therapeutic endoscopy—is both safe and maximally effective for upper gastrointestinal sharp foreign bodies. The successful outcome underscores the critical importance of this management algorithm in preventing progression to life-threatening complications. This case-driven synthesis reinforces that adherence to a rigorous, evidence-based protocol is the most effective strategy to navigate this pointed clinical challenge and consistently achieve optimal patient outcomes.